ANALISIS PERILAKU KONSUMTIF DITINJAU DARI PENGGUNAAN MEDIA SOSIAL INSTAGRAM DAN STATUS SOSIAL EKONOMI - Muhammad Alang Khairun Nizar; Ramadhan Adi Pengestu (Digital Business Progress, 2022)
This study aims to determine how the influence of E-Servicescape and Completeness of Information on Online Shopping decisions at Shopee. The sample in this study were housewives in the Tambangan village, Tebing Tinggi city who used the shopee application with a total of 96 people. Regression analysis method used is multiple linear regression and to test the hypothesis used t test and f test. The research data were analyzed or processed using the SPSS version 25 program. The results showed that e-servicescape had an effect on the purchasing decision variables. The information quality variable has an effect on the purchasing decision variable and the trust factor has no effect on the shopping decision at shopee.